Investigation of Fickian diffusion in the ternary mixtures of water-ethanol-triethylene glycol and its binary pairs; Physical Chemistry Chemical Physics; Vol. 17, iss. 41 - Legro J. K. Ch. Zhan Klod Chislan; Gaponenko Yu. A.; Mialdun A. Aliaksandr; Triller T.; Hammon N.; Kohler Werner; Shevtsova V. M. Valentina (2015, 2015)
Title screen